Intestinal parasitic infections and risk factors among Myanmar migrant workers in northeast Thailand - Wararat Sangwalee; Nathkapach Rattanapitoon; Tongjit Thanchomnang (Asian Pacific Journal of Tropical Medicine, 2021)
Objective: To determine the prevalence and associated factors of intestinal parasitic infections in migrant workers in Nakhon Ratchasima Province, Northeast Thailand. Methods: A cross-sectional study was conducted from August 2017 to July 2018 in 600 Myanmar migrant workers. Questionnaires were employed for collecting the demographic data of participants. Stool samples were collected and examined using the formalin-ether concentration technique. Risk factors for intestinal parasitic infections were determined using multiple logistic regressions analyses. Results: The overall infection rate of intestinal parasitic infections was 27.67% (166/600). Among the intestinal helminthes observed, hookworm was most abundant (8.67%) followed by Trichuris trichiura (8.50%), Opisthorchis viverrini(4.17%), Ascaris lumbricoides(1.50%), Strogyloides stercoralis(1.17%) and Hymenolepis nana(0.5%). Meanwhile, Entamoeba coli was the most prevalent intestinal protozoa (4.33%, 26/600) followed by Endolimax nana (1.33%), Entamoeba histolytica complex (1.17%), Blastocystis sp. (1.0%) and Giardia duodenalis (0.17%). The study found significant associations between gender and Strogyloides stercoralis infection (ORadj=5.61, 95% CI=1.18–26.70, P=0.03), workers aged 30 years old were likely to have a lower risk of the T. trichiura infection (ORadj=0.45, 95% CI= 0.23–0.89). Moreover, the history of consuming raw or undercooked cyprinoid fish was a risk factor of Opisthorchis viverrini infection (ORadj=2.82, 95% CI=1.22–6.49, P=0.015). Conclusions: There remains a high prevalence of intestinal parasitic infections among Myanmar migrant workers in the study area and therefore health screenings for all migrant workers in Thailand are required.